REDES SOCIALES Y SU IMPACTO EN LA CALIDAD DE VIDA DE LOS JÓVENES DEL CANTÓN QUEVEDO DEL SECTOR LOS CHAPULOS AÑO 2022. - Rojas Litardo, Lizbeth Alexandra (2022)
Social networks have had an impact on the quality of life of young people in the Quevedo canton of the Los Chapulos sector by making excessive use of them. The following objective was set for the study: To determine the impact that social networks have on the quality of life of young people in the Quevedo canton of the Los Chapulos sector. The methodology and research techniques used were: deductive, inductive, analytical methods together with descriptive research, which allowed analyzing the problems and causes of why some young people prefer social networks, proceeding to carry out a survey with clear questions, for the selection of the sample was intentionally made to 325 young people from the sector, taking into account the different criteria defined in the methodology. The results show that the majority of those who make use of social networks are young people and adolescents and the little control that exists in their homes influences to affect their quality of life, reflecting on their educational performance, where some of them present a poor academic performance, due to poor grades, in addition to affecting their emotions, behavior, impacting their physical health. It is concluded that social networks have advantages and disadvantages, they facilitate communication so that information can reach everywhere, effectively and immediately. However, it is recommended to raise awareness of their use and greater control of what they observe, through these alternative means of communication, promoting their proper use as educational options, using social networks as social tools that benefit society by strengthening interpersonal relationships. with the rest.